A New Player in the Game: Changing Electoral Competition in Germany - Aiko Wagner; Josephine Lichteblau (The Changing German Voter, 2022)
This chapter asks how electoral competition changed from 2013 to 2017 in East and West Germany. Following Sartori's understanding of party systems as systems of interactions resulting from inter-party competition, it focuses on the content-related properties of the German party system. Combining data from the GLES 2013 and 2017 voter and candidate surveys, it investigates, first, the extent of electoral competition in terms of overlapping electoral support of party pairs and, second, how the establishment of the AfD changed the substantial structure underlying electoral competition in East and West Germany. Findings suggest that electoral competition in Germany is best described as three-dimensional. Whereas regional differences result from different voter preferences regarding policy issues, temporal differences are essentially the result of the changing relevance of the socio-economic and socio-cultural issue dimensions but also a newly emerged populist–pluralist divide.
Additional information: The open access publication of the edited volume "The Changing German Voter" was financially supported by the Leibniz Association's Open Access Publication Fund for Monographs, the University of Mannheim, and the DGfW.; doi:10.4232/1.13232; doi:10.4232/1.12043; doi:10.4232/1.13235; doi:10.4232/1.13089
Keywords: 320; electoral competition; party systems; East and West Germany; dimensionality of competition; AfD